Make Osor great again - Mileusnić, Zrinka (Studia universitatis hereditati, 2025)
Osor, a small settlement, embodies the tension between exceptional archaeological significance and limited contemporary accessibility. Once a key maritime and ecclesiastical centre of the northern Adri- atic, it is today marked by demographic decline, infrastructural constraints, and strong tourism sea- sonality. This article conceptualises accessibility as a multidimensional heritage problem that extends beyond physical access to include interpretation, knowledge circulation, and public engagement. Fo- cusing on digital heritage tools, particularly the concept of a digital twin, it argues that digitally me- diated access can transform archaeological research into a distributed educational and cultural in- frastructure. Osor is presented as a pilot case for rethinking heritage promotion, interpretation and presentation in small and remote sites, aligning archaeological interpretation with sustainability, inno- vation, and learning.
Keywords: accessibility; archaeological heritage; arheološka dediščina; digital heritage; digital twin; digitalna dediščina; digitalni dvojnik; dostopnost; sustainable tourism; trajnostni turizem